Mitigating continuous cropping barriers in tobacco through organic amendments-induced rhizosphere micro-environmental improvement - Huang, Jie; Wang, Xinyue; Yang, Lili; Li, Yuanhuan; Xia, Bing; Li, Hailin; Deng, Xiaohua (Frontiers in Plant Science, 2025)
Organic amendments supply essential nutrients to crops and act as effective soil conditioners. This study investigates the effects and mechanisms of organic amendments on soil physicochemical properties and microbial diversity, aiming to provide technical solutions for alleviating continuous cropping obstacles. A three-year field experiment was conducted with four types of organic amendments: biological organic fertilizer (BF), carbon-polymerized organic water-soluble fertilizer (CF), potassium fulvate from mineral sources (PF), and microbial fertilizer (MF). The control group received no organic fertilizer application. Results showed that compared to the control, organic amendments significantly increased soil organic matter and available nutrient contents, organic matter and available phosphorus under BF (22.5 and 43.2 mg/kg, respectively) showed increases of 129.6% and 53.7%, respectively. Similarly, available potassium in PF (286.6mg/kg) was elevated by 47.3%. Additionally, soil pH was increased (shifting from 5.4 to 6.0), thereby alleviating soil acidification. 16S rRNA and ITS sequencing revealed that organic amendments markedly influenced soil microbial abundance and diversity, increasing the relative abundance of beneficial bacteria (e.g., The abundance of Gemmatimonas rose from 10.0% in control to 19.2% in MF.) while suppressing pathogenic bacteria (e.g., The abundance of Ralstonia decreased from 10.5% in control to 2.5% in MF.). In terms of tobacco growth, organic amendments enhanced root length, surface area, volume, and branching number; Significant increases were observed in α-amylase activity (from 0.6 to 1.6 mg/min/g)) and nitrate reductase activity (from 0.15 to 0.21 U/g) in leaves following the treatment.; and reduced the incidence of bacterial wilt and black shank diseases. Specifically, BF, CF, PF, and MF achieved relative control efficacies of 66.7%, 56.0%, 44.0%, and 61.9% against bacterial wilt, and 66.0%, 52.6%, 42.3%, and 55.7% against black shank, respectively. In conclusion, the application of organic amendments can alleviate continuous cropping barriers by improving the soil micro-environment, promoting tobacco growth, and providing certain control over soil-borne diseases. Overall, the BF treatment showed the most comprehensive improvement effect, and to a lesser extent, PF and MF.